2019
DOI: 10.14260/jemds/2019/341
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index in Thalassemia Children

Abstract: BACKGROUNDThalassemia is more common in populations in the geographic belt from south east Asia to Africa and it is more common in an around Dibrugarh District of Assam, India. Most of the time, children present with either anaemia or failure to thrive especially seen in children belonging to tea garden area. Along with other laboratory parameters, anthropometric measurements are important especially BMI to see the status of the growth pattern. Quetlet index also known as BMI has been in use to study the growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…In the current study it was found that BMI was significantly lower in Patient group than control group. This is in agreement with Dey, Konwar, Sarkar [11] who found that underweight (Low BMI) was a common finding in thlalassemia patients specially when they were older than 10 years of age.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the current study it was found that BMI was significantly lower in Patient group than control group. This is in agreement with Dey, Konwar, Sarkar [11] who found that underweight (Low BMI) was a common finding in thlalassemia patients specially when they were older than 10 years of age.…”
Section: Discussionsupporting
confidence: 92%
“…The cause of under nutrition in thalassemia major patients is multifactorial. Endocrinopathies including hypothyroidism, hypo-gonadotropic gonadism, growth hormone deficiency, hypoparathyroidism are the major causes of under nutrition in these patients [11].…”
Section: Discussionmentioning
confidence: 99%
“…They found that 48.2% were malnourished with a mean BMI of 13.9 ± 1.6 kg/m 2 . TM has a significant impact on the growth process of children, and hence early intervention is needed to reduce the prevalence of malnutrition as good nutrition with adequate vitamin and trace element intake, along with calcium and vitamin D supplementation, side by side with optimal iron chelating therapy [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, pre-diabetic states are also at increased risk of cardiovascular disease [ 31 ]. Endocrine abnormalities should be monitored carefully, and a thorough endocrine evaluation should be carried out yearly in every patient with TM to detect subclinical endocrinopathies [ 26 ]. Early identification and treatment of persons with prediabetes has the potential to reduce or delay the progression to diabetes [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to WHO classification, anaemia is defined as a condition where the erythrocytes number or the haemoglobin levels are under the normal average. WHO considered about 42% of the world's children aged 5 years old and 40% of pregnant women as anaemic [16]. Severity of anaemia categorized into three groups: mild with haemoglobin level of 11-11.9 g/dL; moderate (8-10.9 g/dL) and lastly the severe level of anaemia which ranges less than 8 g/dL [9].…”
Section: Figure 2 Transfusion Requirement In Non-transfusion-dependen...mentioning
confidence: 99%